2007
DOI: 10.1007/s00439-007-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

A new locus for split hand/foot malformation with long bone deficiency (SHFLD) at 2q14.2 identified from a chromosome translocation

Abstract: Split hand/foot malformation (SHFM) with long bone deWciency (SHFLD) is a distinct entity in the spectrum of ectrodactylous limb malformations characterised by associated tibial a/hypoplasia. Pedigrees with multiple individuals aVected by SHFLD often include nonpenetrant intermediate relatives, making genetic mapping diYcult. Here we report a sporadic patient with SHFLD who carries a de novo chromosomal translocation t(2;18)(q14.2;p11.2). Characterisation of the breakpoints revealed that neither disrupts any k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…An apparently balanced de novo translocation with a breakpoint at 2q14.2 was identified in a patient with SHFM and holoprosencephaly (HPE) [Corona-Rivera et al, 2000]. A patient with SHFLD was later found to have a balanced translocation that also involved 2q14.2 [Babbs et al, 2007]. Although no genes were interrupted, the breakpoint was located within a region homologous to the Dominant hemimelia locus in mice.…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…An apparently balanced de novo translocation with a breakpoint at 2q14.2 was identified in a patient with SHFM and holoprosencephaly (HPE) [Corona-Rivera et al, 2000]. A patient with SHFLD was later found to have a balanced translocation that also involved 2q14.2 [Babbs et al, 2007]. Although no genes were interrupted, the breakpoint was located within a region homologous to the Dominant hemimelia locus in mice.…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…Although no genes were interrupted, the breakpoint was located within a region homologous to the Dominant hemimelia locus in mice. Absence of mutations in several candidate genes in the region, including GLI2 and INHBB, in other patients with SHFM/SHFLD suggested that the translocation may have caused SHFLD through a position effect mechanism [Babbs et al, 2007]. A third balanced translocation involving 2q14.2 was identified in a fetus with isolated bilateral split-foot malformations [David et al, 2009].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…The breakpoint associated with SFM was mapped to position 120 922 kb and colocalizes with a recently reported breakpoint associated with SHFLD. 11 The second breakpoint, associated with HHES, was mapped to position 118.4 Mb of chromosome 2, which is actually distal 2q41.1 and not 2q41.2. Several strong candidate genes were identified in these loci, including GLI2, INHBB, INSIG2 and EN1, which can all be easily correlated with Sonic Hedgehog (SHH) signalling and the observed phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 2q14.2 has been implicated in a single individual with SHFLD arising from a de novo translocation without disrupting any known genes, but corresponding to the homologous region in mouse which gives rise to the 'dominant hemimelia' (Dh) limb malformation. 10 Both 1q42.2-q43 and 6q14.1, designated as loci SHFLD1 and SHFLD2, respectively, were shown to be linked to SHFLD in a large consanguineous Arab family. 11,12 SHFLD3 was mapped in a Brazilian family to an 861 kb interval at 17p13.1-17p13.3.…”
Section: Introductionmentioning
confidence: 99%